2002
DOI: 10.1021/ja017706t
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport through Self-Assembled Monolayers of Compounds of Interest in Molecular Electronics

Abstract: The electrical properties of self-assembled monolayers (SAMs) on metal surfaces have been explored for a series of molecules to address the relation between the behavior of a molecule and its structure. We probed interfacial electron transfer processes, particularly those involving unoccupied states, of SAMs of thiolates or arylates on Au by using shear force-based scanning probe microscopy (SPM) combined with current-voltage (i-V) and current-distance (i-d) measurements. The i-V curves of hexadecanethiol in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
338
3
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(357 citation statements)
references
References 58 publications
13
338
3
3
Order By: Relevance
“…In principle, one approach to manipulating the shape of the tunneling barrier, and thus to influencing the rate of charge transport, is to introduce functional groups into the structure of the SAM that are capable of influencing this topography, and thus the rate or mechanism of charge transport. [25][26][27][28][29] Using Ga 2 O 3 /EGaIn top-electrodes, however, we found previously that the tunneling current is insensitive to the incorporation of several functional groups familiar in organic chemistry 4,8 (e.g., an amide, -CONH-or -NHCO-) in the backbone of the molecules in the SAM, or a variety of functional groups (both aliphatic and aromatic) that are not electrochemically active at the terminus of the SAM ostensibly in contact with the Ga 2 O 3 film. bidentate ionic binding coordination of the carboxylate to the surface.…”
Section: Studies Of Charge Tunneling Through Self-assembled Monolayermentioning
confidence: 99%
“…In principle, one approach to manipulating the shape of the tunneling barrier, and thus to influencing the rate of charge transport, is to introduce functional groups into the structure of the SAM that are capable of influencing this topography, and thus the rate or mechanism of charge transport. [25][26][27][28][29] Using Ga 2 O 3 /EGaIn top-electrodes, however, we found previously that the tunneling current is insensitive to the incorporation of several functional groups familiar in organic chemistry 4,8 (e.g., an amide, -CONH-or -NHCO-) in the backbone of the molecules in the SAM, or a variety of functional groups (both aliphatic and aromatic) that are not electrochemically active at the terminus of the SAM ostensibly in contact with the Ga 2 O 3 film. bidentate ionic binding coordination of the carboxylate to the surface.…”
Section: Studies Of Charge Tunneling Through Self-assembled Monolayermentioning
confidence: 99%
“…There are mainly two approaches for wiring molecules between electrodes. One method is to make top-contact junctions, which includes scanning probe microscopy (scanning tunneling microscopy (STM) and conducting atomic force microscopy (AFM)), [11][12][13][14][15][16][17][18][19][20][21][22] cross wire junctions, [23][24][25] mercury drop electrodes [26,27] and thermally deposited metal films. [6] All devices manufactured by this kind of method can be categorized as 'prototype devices', which are very useful for fundamental investigations and have already provided many important results.…”
Section: Introductionmentioning
confidence: 99%
“…[6] All devices manufactured by this kind of method can be categorized as 'prototype devices', which are very useful for fundamental investigations and have already provided many important results. [4][5][6][7][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However, these devices are far from practical applications, as we can not imagine a nanometer device carrying a huge scanning probe microscopy (SPM) system or other systems. The other way utilizes nanogap electrodes [28][29][30][31][32] to form metal/molecule/metal devices.…”
Section: Introductionmentioning
confidence: 99%
“…It was, however, shown that estimation of the electrical conductance of adsorbed molecules by use of STM is quite complicated compared with techniques in which the electrode is directly attached to the molecules [267][268][269][270][271]. C-AFM has been found to be a good candidate for direct measurement of electrical conduction by organic monolayers such as SAMs [25,[277][278][279][280][281][282][283][284][285][286][287][288]. The advantages of C-AFM over STM are that the electronic properties of a molecular function are sensitive to the effects of deformation caused by the force of interaction between the tip and the sample [25,285,287].…”
Section: Self Assembled Monolayersmentioning
confidence: 99%